2012
DOI: 10.1007/s10561-012-9312-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of accelerated electron beam on mechanical properties of human cortical bone: influence of different processing methods

Abstract: Accelerated electron beam (EB) irradiation has been a sufficient method used for sterilisation of human tissue grafts for many years in a number of tissue banks. Accelerated EB, in contrast to more often used gamma photons, is a form of ionizing radiation that is characterized by lower penetration, however it is more effective in producing ionisation and to reach the same level of sterility, the exposition time of irradiated product is shorter. There are several factors, including dose and temperature of irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…Other studies (Dziedzic-Goclawska et al 2005 ; Kaminski et al 2012a , b ), as well as the presented case report, proved that the concerns are groundless. Frozen bone grafts radiation-sterilised even with as high dose as 35 kGy were entirely safe for the recipient’s health and its structure provided excellent scaffold for the new bone formed in the process of osteoinduction.…”
Section: Discussionsupporting
confidence: 64%
“…Other studies (Dziedzic-Goclawska et al 2005 ; Kaminski et al 2012a , b ), as well as the presented case report, proved that the concerns are groundless. Frozen bone grafts radiation-sterilised even with as high dose as 35 kGy were entirely safe for the recipient’s health and its structure provided excellent scaffold for the new bone formed in the process of osteoinduction.…”
Section: Discussionsupporting
confidence: 64%
“…Two studies indicated recovery of cadaveric tissues in processing labs (Guo et al 2012; Kaminski et al 2012). Twelve studies indicated that during recovery, allografts were recovered under aseptic conditions, but did not address specific methods to reduce the bioburden.…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies indicated that during recovery, allografts were recovered under aseptic conditions, but did not address specific methods to reduce the bioburden. Only one study reported the use of class C and D air filters to reduce potential contamination of tissues by airborne contaminant (Kaminski et al 2012). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early concerns regarding the limited penetrability of dense materials by electrons have been addressed through process improvements, including increasing the power of the electron beam to 10 MeV and incorporating two-sided dose delivery 27 . Several medical device companies have successfully adopted e-beam technology to terminally sterilize their tissuebased products because of the benefits of reduced tissue degradation, well-controlled dose ranges, and rapid turnaround 25,28 . Encouraged by this progress, our organization has validated that e-beam sterilization of soft-tissue allografts at delivered doses between 9.2 and 21.0 kGy achieves a sterility assurance level (SAL) of 10 26 , as measured in accordance with the ANSI/AAMI/ISO (American National Standards Institute/Association for the Advancement of Medical Instrumentation/International Organization for Standardization) 11137 standards.…”
mentioning
confidence: 99%